Identification of Neisseria meningitidis Serogroups Y and W135 by siaD Nucleotide Sequence Analysis - Lewis, C. (American Society for Microbiology, 2003)
Rapid serogrouping of meningococci is essential for the effective public health management of cases of the disease and the contacts of infected patients. Here we describe an accurate nucleotide-sequencing method for the confirmation of serogroup Y and W135 meningococci by siaD gene analysis from cultures of Neisseria meningitidis.